Subcutaneous treprostinil for the treatment of severe non-operable chronic thromboembolic pulmonary hypertension (CTREPH): a double-blind, phase 3, randomised controlled trial. Issue 3 (March 2019) - Sadushi-Kolici, Roela; Jansa, Pavel; Kopec, Grzegorz; Torbicki, Adam; Skoro-Sajer, Nika; Campean, Ioana-Alexandra; Halank, Michael; Simkova, Iveta; Karlocai, Kristof; Steringer-Mascherbauer, Regina; Samarzija, Miroslav; Salobir, Barbara; et al.
Summary: Background: Treprostinil, a prostacyclin analogue, is effective for the treatment of pulmonary arterial hypertension. However, information is scarce regarding treprostinil for treatment of chronic thromboembolic pulmonary hypertension (CTEPH). The aim of this study was to examine the efficacy and safety of subcutaneous treprostinil in this setting. Methods: In this 24-week, randomised, double-blind controlled trial, we enrolled patients with CTEPH, classified as non-operable, or with persistent or recurrent pulmonary hypertension after pulmonary endarterectomy, in six European expert centres in Austria, Czech Republic, Germany, and Poland. Patients in WHO functional class III or IV with a 6-min walk distance of 150–400 m were randomly assigned at a 1:1 allocation ratio to continuous high-dose subcutaneous treprostinil (target dose around 30 ng/kg per min at week 12) or low-dose subcutaneous treprostinil (target dose around 3 ng/kg per min at week 12). The primary endpoint was the change from baseline in 6-min walk distance at week 24. All patients who received at least one dose of the study drug were included in the intention-to-treat efficacy and safety analyses based on assessment of adverse events. The trial was registered atClinicalTrialsRegister.eu EudraCT number 2008-006441-10 andClinicalTrials.gov, numberNCT01416636 . Findings: From March 9, 2009, to June 9, 2016, 105 patients were enrolled with 53 (50%) patients randomly assigned to high-dose and 52 (50%) patients to low-dose subcutaneous treprostinil. At week 24, marginal mean 6-min walk distance improved by 44·98 m (95% CI 27·52 to 62·45) in the high-dose group, and by 4·29 m (95% CI −13·34 to 21·92) in the low-dose group (treatment effect 40·69 m, 95% CI 15·86 to 65·53, p=0·0016). 12 serious adverse events were reported in ten (19%) of 52 patients from the low-dose group and 16 serious adverse events were reported in nine (17%) of 53 patients from the high-dose group. The most common treatment-related adverse events in both groups were infusion site pain and other infusion site reactions. Interpretation: Treatment with subcutaneous treprostinil was safe, and improved exercise capacity in patients with severe CTEPH. Subcutaneous treprostinil provides a parenteral treatment option for patients of WHO functional class III or IV and those who do not tolerate other therapies or need combination treatment. Funding: SciPharm Sàrl.